Evaluation of the Nature and Concentration of the Surfactant on the Properties of Red Mud/Metakaolin Porous Geopolymers Foamed with Aluminium - Bilici, Senem; Carvalheiras, Joao; Labrincha, Joao A.; Novais, Rui M. (MDPI, 2022)
The chemical foaming technique is possibly the most common method of producing porous geopolymers. Despite this, to date, the role of the content and type of surfactant on the pore size distribution of porous geopolymers is not fully perceived, as constant surfactant dosages are usually employed. In addition, the comparison of literature studies is challenging since a distinct mixture of designs is employed. This investigation intends to provide additional insights on the topic, focusing on synthesizing red mud/metakaolin geopolymer foams and envisioning their use in thermal insulating applications. Various mixtures were prepared using three commercially available surfactants, namely Hostapur OSB, sodium dodecyl sulfate (SDS), and Triton X114. The content of the surfactant (0.025, 0.05, and 0.075 wt.%) and the amount of the foaming agent (aluminum powder, Al; 0.05, 0.075, and 0.10 wt.%) was modified, keeping the binder composition constant and the physical properties of the produced geopolymers were characterized. Results show that the combination between sodium dodecyl sulfate (0.025 wt.%) and aluminum (0.10 wt.%) leads to the strongest reduction in the foam density, the lowest value here reported being -400 kg/m(3). On the other hand, samples produced with Hostapur OSB have much higher open porosity (up to 47.7%) and water absorption (up to 80.4%) values, showing that this surfactant leads to a pore network with higher connectivity. In addition, the microstructure of the foams, particularly pore morphology (size and shape) and connectivity between the produced pores are highly dependent on the type of surfactant, sodium dodecyl sulfate generating coarser pore size distribution with round, but mostly closed pores, while a narrower pore size distribution coupled with smaller size pores is seen with the Hostapur. These results suggest the feasibility of tuning the foams' properties (porosity and mechanical performance) according to the application by the proper combination of the type of surfactant and their concentration, enabling their use as thermal and acoustic insulators or as filters/membranes in wastewater treatment systems.
Keywords: alkali-activated material; red mud; pore size distribution; water absorption; thermal conductivity; STRUCTURAL CHARACTERISTICS; INSULATING PROPERTIES; COMPRESSIVE STRENGTH; POROSITY; AGENT; WATER; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering; Physics